2015
DOI: 10.1007/s10517-015-3118-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxanthine on Functional Activity of Nucleoside Transporters ENT1 and ENT2 in Caco-2 Polar Epithelial Intestinal Cells

Abstract: We studied regulation of hypoxanthine transport depending on its concentration in the culture medium. Caco-2 cells were differentiated on membrane filters to create a model of the intestine. Different hypoxanthine uptake on the apical and basolateral cell membranes was observed. The expression of SLC29 family genes encoding passive nucleoside transporters increased upon changes in hypoxanthine concentration in the medium Localization of the transporters and their influence on the effect of pharmacological prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The vector controls did not exhibit downregulation of the other genes seen in the SLC43A3transfected cells. The downregulation of ENT2 and MRP4 may reflect compensation by the cells to the enhanced availability of nucleobases via ENBT1 to support intracellular metabolism (Senyavina and Tonevitskaya, 2015). Both of Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The vector controls did not exhibit downregulation of the other genes seen in the SLC43A3transfected cells. The downregulation of ENT2 and MRP4 may reflect compensation by the cells to the enhanced availability of nucleobases via ENBT1 to support intracellular metabolism (Senyavina and Tonevitskaya, 2015). Both of Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Predominant apical localization of ENT2 in these cells was reported [11]. Previous studies of hypoxanthine transport fl uxes in Caco-2 cells showed high concentration of ENT transporters on the basolateral membrane of Caco-2 cells and their functional activity on the apical membrane [1]; however, the expression and localization of individual transporters remain unclear.…”
Section: Resultsmentioning
confidence: 94%
“…In view of the data on apical (16±1.3 nmol/mln cells) and basolateral (31.8±6.7 nmol/mln cells) hypoxanthine concentrations in different media in 24 h [1], the amount of transporter ENT2 (n 2 b ) on the basolateral membrane was calculated from (3): ENT-2 bas =(7.0±1.0)×10 -13 μmol/cell. Equation (4) refl ects the relationship between the apical content of transporters ENT1 and ENT2, and [8], which corresponds to 16×10 -13 μmol/ cell and qualitatively agrees with the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations